Community Empowerment of Ngingit Village, Tumpang District, Malang Regency through Suweg Processed Products in the Framework of Raising the Existence of Local Food Ingredients Towards a Food Self-Sufficiency Village - Pratikno, Mochammad Yosi; Astuti, Ani Budi; Akrimah, Yasma Aziza Ul; Seftyaningtyas, Endryana; Alvia, Siva Nur; Putro, Bayu Hangga Trio Eko (Journal of Innovation and Applied Technology, 2022)
The program carried out to overcome food problems is CAMPA. The CAMPA program provides training on the processing of local food ingredients, namely suweg into several preparations such as noodles, meatballs, cookies, and cereals. The method used in this study is the Participatory Action Research (PAR) method, a method that involves the dominant role of the community in the concept of empowerment